Continuous Synthesis of Uniformly Dispersed Mesoporous SBA-15 Supported Silver Nanoparticles in a Coiled Flow Inverter Reactor - Zhu, Hai; Wu, Ke-Jun; He, Chao-Hong (Frontiers in Chemistry, 2021)
Mesoporous silica supported nanocatalysts have shown great potential in industrial processes due to their unique properties, such as high surface area, large pore volume, good chemomechanical stability and so on. Controllable and tunable synthesis of supported nanocatalysts is a crucial problem. Continuous synthesis of supported nanoparticles has been reported to get uniformly dispersed nanomaterials. Here, a method for continuous synthesis of uniformly dispersed mesoporous SBA-15 supported silver nanoparticles in a coiled flow inverter (CFI) microreactor is described. Compared to Ag/SBA-15 synthesized in the conventional batch reactor and Ag synthesized in continuous flow, mesoporous silica nanocatalysts synthesized in continuous flow are found to have smaller average size (7-11 nm) and narrower size distribution. The addition of capping agents can effectively change the characteristic of catalysts. Moreover, two kinds of support with different surface area and pore size have been added into the continuous synthesis. This method can provide further understandings for the synthesis of uniformly dispersed supported nanocatalysts in continuous flow, especially for mesoporous nanomaterials.